Annual report on development of new media in China 2011. - Yugong, Yin. Ph.d (China New Technology and New Media., 2013)
It's projected that China's internet population will hit 718 million by 2013, comfortably the largest base of net users in the world. Central to this are issues of ownership, freedom and censorship. But what is China's perspective and on the proliferation of new media within China and what are its concerns? This revealing book outlines the phenomenal recent digital developments seen across China and the vast amount of new media and internet usage. Annual Report on Development of New Media in China (Volume 1) presents a clear analysis of the key characteristics and trends found in present day C.